Political Tribes - Amy Chua (Penguin Press, 2018)
Humans are tribal. We need to belong to groups. In many parts of the world, the group identities that matter most â€“ the ones that people will kill and die for â€“ are ethnic, religious, sectarian, or clan-based. But because America tends to see the world in terms of nation-states engaged in great ideological battles â€“ Capitalism vs. Communism, Democracy vs. Authoritarianism, the â€œFree Worldâ€ vs. the â€œAxis of Evilâ€ â€“ we are often spectacularly blind to the power of tribal politics. Time and again this blindness has undermined American foreign policy. ust as Washingtonâ€™s foreign policy establishment has been blind to the power of tribal politics outside the country, so too have American political elites been oblivious to the group identities that matter most to ordinary Americans â€“ and that are tearing the United States apart. As the stunning rise of Donald Trump laid bare, identity politics have seized both the American left and right in an especially dangerous, racially inflected way. In America today, every group feels threatened: whites and blacks, Latinos and Asians, men and women, liberals and conservatives, and so on. There is a pervasive sense of collective persecution and discrimination. On the left, this has given rise to increasingly radical and exclusionary rhetoric of privilege and cultural appropriation. On the right, it has fueled a disturbing rise in xenophobia and white nationalism.